Respiratory Symptoms and Urinary Cotinine Levels in Pre-school Children Exposed to Environmental Tobacco Smoke - XIAO, SY (Frontiers in Public Health, 2021)
Objective: Preschool children exposed to environmental tobacco smoke (ETS) are at risk of developing adverse respiratory health effects. The present study aimed to investigate the relationship between the effects of cigarette-smoking caregivers on respiratory symptoms and urinary cotinine (UC) levels in children. Methods: A cross-sectional study consisting of 543 children (aged between 5 and 6 years) from 5 kindergartens in central China was conducted using a structured questionnaire. We also analyzed UC levels to investigate the relationship between respiratory symptoms and ETS exposure. We further performed logistic regression analyses to establish the relationship between respiratory symptoms (coughing, rhinorrhea, and sneezing) and UC levels. Results: A total of 71 (13.08%) children had a history of hospital admission with respiratory illnesses including bronchitis and pneumonia over the last 6 months. In addition, 102 (18.78%) children presented coughing symptoms, 114 (20.99%) experienced rhinorrhea and 79 (14.55%) presented sneezing symptoms over the last 6 months. After adjusting the confounders, odds ratio (OR) indicated that the number of cigarettes smoked by a caregiver was associated with coughing (OR=11.02; 95% CI, 3.72-33.66), rhinorrhea (OR=41.83; 95% CI, 5.58-313.55) and sneezing (OR=4.71; 95% CI, 1.33-16.48). Furthermore, UC levels in children with coughing, rhinorrhea and sneezing were significantly higher than in children without respiratory symptoms (P=0.002, P<0.001, P<0.001 respectively). Conclusions: This study reveals that children exposed to ETS have higher levels of UC. Compared with caregiver who non-smoked live with children, smoked cigarettes were highly risk of developing respiratory illnesses in children. Notably, the higher the UC levels the greater the respiratory risk. Our results also signify that UC can be used as an indicator of ETS exposure to inform caregivers of the associated risks, and inform efforts to reduce related effects.